STUDI PENGGUNAAN FOAM SEBAGAI SACRIFICIAL FLUID PADA PEMBORAN TEKNIK MANAGED PRESSURE DRILLING JENIS PRESSURIZED MUD CAP DRILLING - Ihsan Gemilang, Andra
Pressurized Mud Cap Drilling (PMCD) is one of Managed Pressure Drilling (MPD) method that used to control a well that have a total lost circulation problem. Fresh water or brine as a sacrificial fluid will be pumped through drillpipe to transport cutting into vuggy and fracture zone. Annulus is filled with a hi-vis fluid and also back pressure will be applied in annulus to overcome pore pressure of formation. While kick is migrating into annulus, mud cap fluid will be injected via annulus to push gas influx flow to vugular formation. A potential problem may be occurred when using water as sacrificial fluid. Since water is a non-viscous fluid, it will need a high fluid rate to lift cutting, and the cutting lifting is not guaranteed perfectly succeed although the fluid is pumped in a high fluid rate. This paper will discuss foam as one of alternative solution of cutting lifting problem in PMCD technique. This paper will discuss determination of minimum fluid rate, hydrodynamic pressure, and minimum pump power required to pumping foam as a sacrificial fluid. This paper also will discuss which parameter will have most influence in determining minimum fluid rate of foam. Method that been used in writing this paper is literature study, derivation of equation, case study, and sensitivity test.